(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
This study aims to analyze the influence of environmental attributes in sustainable tourism on vivid memory and its impact on the behavioral intentions of international tourists visiting Likupang and Manado. The research employed a quantitative survey method conducted both online and onsite, involving 140 international tourist respondents who visited Likupang or Manado. The findings indicate a significant relationship between environmental attributes, vivid memory, and tourists’ behavioral intentions. These results provide valuable insights for tourism managers and policymakers in enhancing the appeal of sustainable tourism through environmental attributes to influence tourists’ behavioral intentions. Furthermore, the study highlights the role of vivid memory in shaping tourists’ future decisions to visit other destinations in Indonesia.